Energy Analysis of Device Discovery for Bluetooth Low Energy - Jia Liu; Canfeng Chen; Yan Ma; Ying Xu (2013 IEEE 78th Vehicular Technology Conference (VTC Fall), 2013)
Bluetooth Low Energy (BLE) is drawing more and more attention due to its recent appearance in consumer electronic products. As a low-power wireless solution, BLE provides attractive energy performance that makes it particularly suitable for portable, battery-driven electronic devices. Although there are some prior arts focusing on BLE energy performance, it still lacks a thorough study on the important aspect of device discovery. Such energy cost, introduced by intermittent scanning or connection setup, could seriously affect the battery endurance ability of the devices. In this paper, we present quantitative analysis on the neighbor discovery energy for BLE. The modeling results that built upon measurement of CC2541 Mini-Development Kit have been validated quite accurate via extensive experiments. In addition, several interesting conclusions are found while investigating the achieved energy model, which may provide precious guidelines to the design of energy-efficient applications for BLE.